Fluoxetine affects intestinal motility via 5-HT3 and muscarinic receptors in ex vivo mouse model - Pissared Khuituan,; Chotika Nhaemchei,; Sakda Pradab,; Sakena K-da,; Nipaporn Konthapakdee, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Fluoxetine, a selective serotonin reuptake inhibitor anti-depressant, causes undesirable side effects, including diarrhea and constipation. This research investigated the direct effects of fluoxetine at 0.001, 0.01, 0.1, 1, 10, and 100 μM on duodenal and proximal colonic tissue contractions. The investigation aimed to determine related mechanisms using an isolated mouse intestine model. Our study showed that fluoxetine at 0.001 μM increased the amplitude of contraction in colonic tissue but decreased the amplitude in duodenal tissue. The direct application of higher concentrations of fluoxetine (1, 10, and 100 μM) reduced the amplitude of contractions in proximal colonic tissue. Moreover, we found that the stimulatory effect of 0.001 μM fluoxetine on the tone of contractions could be prevented by pre-incubating the tissue in ondansetron and atropine. Our findings suggest that the inhibition of the effect of fluoxetine was mainly mediated via 5-HT3 receptors and muscarinic signaling. These findings might explain the conflicting gastrointestinal symptoms caused by fluoxetine.